Legal and Regulatory Challenges in Combating Financial Cyber Crimes (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In today's modern world, cyberspace is increasingly exerting its influence over every aspect ofhuman endeavour. The internet is bringing about a major and irreversible shift not just in the economicenvironment but also in the underlying premises upon which enterprises are founded. E-commerce hasemerged as a key component of the new electronic economy that has emerged as a result of thistransformation of the industrial economy. Cyberspace is the domain that can be found behind thecomputer screen, on the other side of the telephone receiver, and just a centimetre beneath the surfaceof the keyboard. It is a place where all types of coded phenomena, including words, sounds, and images,may be found dancing. In principle, cyberspace has no limits whatsoever. Everything that can bereduced to zeros and ones will ultimately find a home here this includes everything that can bemeasured, defined, and traded. With the increased dependence on e-commerce and e-governance, awide variety of legal issues related to use of the internet as well as other forms of computer or digitalprocessing devices have emerged. These issues include violations of intellectual property, piracy,freedom of expression, jurisdiction, and others, and they need to be tackled through the interdisciplinaryfield of information law. In the present new millennium, information technology advanced by computernetwork undoubtedly pervades every aspect of society and governance.